Marine Phosphates in the Paleogene oflsla Grande de Tîerra del Fuego - Olivero, E.B. (1998)
Phosphate prospecting in marine sedimentary rocks of the Marginal and Austral basins of the Isla Grande de Tierra del Fuego resulted in the first discovery of phosphatic beds in the Paleogene Rio Claro Formation. Phosphatic anomalies of up to 20.1% P2U5 in concretions and up to 2% PaOs in bulk rock offer promising opportunities for systematic prospection on the Isla Grande de Tierra del Fuego. The phosphatic beds are conglomerates, coquinas and conglomeratic sandstones interbedded with thick mudstone packets. They belong to the condensed-type phosphatic beds, which are the product of erosion and reworking of concretions developed in fine sediments. Phosphate concretions containing glauconite, together with abundant glauconite in the same and closely associated beds, indicate a common syn-sedimentary to earlydiagenetic origin for both minerals, via recycling of sedimentary iron. This process occurred on a shelf with low sedimentation rates, pointing to high sea-level stands and marked interruptions in the sedimentation of the thick Paleogene sedimentary sequence of the Austral Basin . The deposit point to the existence and extension of this early Cenozoic phosphogenic episode to high latitudes in the Southern Hemisphere. © 1998 Asociacidn Geoldgica Argentina.